Undergraduate students ability to process information and its relation with visual and verbal representation in plant morphology laboratory activity - S Ladisa; A Rahmat; B Supriatno (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Laboratory activity of plant morphology requires students to process the information of specimen in their working memory and then represent it both visually and verbally. The aim of the study is to describe the relation between the student’s ability of information processing and their visual and verbal representation in plant morphology laboratory activity. This study was conducted in one of the state univercities in Bandung Indonesia, in the class of pant morphology course with 31 students. Student’s ability of information processing was assessed by using task complecity which consist of component of information, integration of information, and application of information. The visual representation was analyzed based on authenticity and the detail of picture, propotional of picture, and suitability of the picture with the concept. The verbal representation was analyzed by the suitability of the description with the concept, completeness of the description, clarity of the description, terminology, and binominal nomenclature. The result shows that the student’s information processing ability has low correlation with visual and verbal representation ability. Based on the result, we can say that student’s with a good information processing ability can’t always show that they have a good visual and verbal representation ability as well